The Sunny Side of Negative Feedback: Negative Feedback Enhances One’s Motivation to Win in Another Activity - Fang, Hui; Li, Ximei; Ma, Haiying; Fu, Huijian (Frontiers in Human Neuroscience, 2021)
Negative feedback has been widely reported to be a demotivator that could frustrate the recipient’s need for competence and erode his intrinsic motivation in the same activity. Nevertheless, little attention has been devoted to the intertemporal effect of negative feedback on one’s intrinsic motivation in another activity. To fill this gap, we arranged participants in a game with two sessions and manipulated the content of feedback as a between-subject factor. In session 1, participants had to complete a time estimation task with moderate difficulty, during which half of the participants received normal performance feedback and the other half received negative performance feedback. In session 2, all participants were guided to accomplish a moderately difficult stopwatch task that was competence-supportive. A more pronounced win-loss difference wave of reward positivity (RewP) was detected in the experimental (negative performance feedback) group compared to the control (normal performance feedback) group during session 2. This finding indicates that negative feedback in an activity may have a positive impact on one’s intrinsic motivation in a following competence-supportive activity.